Herpes simplex virus 1 interaction with Toll-like receptor 2 contributes to lethal encephalitis - Kurt-Jones, Evelyn A. (National Academy of Sciences, 2004)
Human neonates infected with herpes simplex virus 1 (HSV-1) develop one of three distinct patterns of infection: (i) infection limited to the skin, eye or mouth; (ii) infection of the CNS; or (iii) disseminated infection. The disseminated form usually involves the liver, adrenal gland, and lung, and resembles the clinical picture of bacterial sepsis. This spectrum of symptoms in HSV-1-infected neonates suggests that inflammatory cytokines play a significant role in the pathogenesis of the disease. Recent studies suggest that the Toll-like receptors (TLRs) may play an important role in the induction of inflammatory cytokines in response to viruses. TLRs are mammalian homologues of Toll, a Drosophila protein that is essential for host defense against infection. Engagement of TLRs by bacterial, viral, or fungal components leads to the production and release of cytokines and other antimicrobial products. Here, we demonstrate that TLR2 mediates the inflammatory cytokine response to HSV-1 by using both transfected cell lines and knockout mice. Studies of infected mice revealed that HSV-1 induced a blunted cytokine response in TLR2(–/–) mice. Brain levels of monocyte chemoattractant protein 1 chemokine were significantly lower in TLR2(–/–) mice than in either wild-type or TLR4(–/–) mice. TLR2(–/–) mice had reduced mortality compared with wild-type mice. The differences between TLR2(–/–) mice and both wild-type and TLR4(–/–) mice in the induction of monocyte chemoattractant protein 1, brain inflammation, or mortality could not be accounted for on the basis of virus levels. Thus, these studies suggest the TLR2-mediated cytokine response to HSV-1 is detrimental to the host.